The effects of credit cards on the sales revenue of Iloilo City business establishments - Verjes, Mary Cleofe L.; Vego, Happy B.; Superficial, Rheenin C.; Panes, Irene M.; Delfin, Jogi A.
Executive summary-The survey conducted was composed of 30 respondents comprising every category. There are four categories namely : the cardholders, the non-cardholders, establishment accepting credit cards and establishment not accepting credit cards. Corresponding, four set of questionnaires were prepared. The customer respondents were randomly chosen as to age, sex, civil status, occupation and residence. Some customer respondents do not reside in Iloilo. The researchers assumed that the customers of business establishment in Iloilo City comprise not only those who live in Iloilo City but also those residing in the neighboring provinces-the whole area of Region VI. However, respondents of business establishments should be conducting and performing business in Iloilo City. Demographic and socio-economic factors were determined which assisted the researchers in their pursuit to come up with a reasonable basis for conclusion and recommendation. Cardholder respondents, specifically, were all employed and financially stable individuals. These include business executives, government employees, engineers, medical representatives, among others. Their income bracket mostly range from P15,000-P20,000 a month yet roughly half do not own a car. They go out of town on an occasional basis and spend most on their shopping sprees. They opt to own a credit card because of its convenience and flexibility. Accessibility is their top priority when they chose their type of credit card. Most cardholders have credit limit between P10,000-P20,000 which also vary depending on their capacity to pay. Non card-holders on the other hand, expressed their desire to own a credit card because of its convenience and financial accessibility. But then, its not necessary for their kind of lifestyle. They are also employed, income deriving individuals and have income bracket ranging from P5.001-P10,000. Most of them do not own a car and also go out of town on an occasional basis. Their expenditures is largely covered by their shopping sprees and bills. For credit cards choice, they go after Diners Club International, MasterCard and American Express. Their choice is affected by the card's accessibility and peer influence. They also admitted that having credit cards are advantageous in the present trend of financial system. Most non-card accepting establishments are sole proprietorship entities which are mostly involve in merchandising. Their primary target markets are the middle class and the masses. They perceived that accepting credit cards are inconvenient and complex which served as a premise for their non-acceptance nor any desire to accept credit cards. Their customers are basically non-cardholders which made acceptance of credit card unnecessary. For them, credit cards are not advantageous which will only complicate further their business transactions. The business establishments in Iloilo City which accept credit card are mostly located in the major malls and shopping centers of Iloilo City. Their primary target market are the elites and the upper middle class.